2013
DOI: 10.2174/1876816420130418001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Alterations and Oxidative Stress in Acute Leukemia

Abstract: Mitochondrial DNA (mtDNA) alterations were reported in many cancers but their roles in oncogenesis are still debated. We aimed to examine qualitative and quantitative mtDNA modifications and oxidative stress in normal and cancer cells.23 leukemia patients and 18 healthy subjects were recruited from the hospital of Azziza Othmana (Tunisia). Mitochondrial D-loop was sequenced, mtDNA level was determined by Q-PCR, the oxidative stress was assessed by a fluorescent probe and the mitochondrial transcription factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Reactive oxygen species (ROS) has long been known to be involved in the pathophysiology of cancer (Valko et al, 2006). The most common cancers in children are leukemia and the oxidative stress is a crucial feature of ALL (Battisti et al, 2008;Mazor et al, 2008;Saadaoui et al, 2013). Meanwhile recent advances in the field of reproductive medicine have focused the attention of many researchers to consider ROS as one of the mediators of infertility causing sperm dysfunction (Agarwal and Prabakaran, 2005;Singh, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) has long been known to be involved in the pathophysiology of cancer (Valko et al, 2006). The most common cancers in children are leukemia and the oxidative stress is a crucial feature of ALL (Battisti et al, 2008;Mazor et al, 2008;Saadaoui et al, 2013). Meanwhile recent advances in the field of reproductive medicine have focused the attention of many researchers to consider ROS as one of the mediators of infertility causing sperm dysfunction (Agarwal and Prabakaran, 2005;Singh, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in mitochondrial mass and MtDNA content may be an early molecular event of human cells in response to endogenous or exogenous oxidative stress. Exposure to benzene increases the generation of ROS in the mitochondria and increases the risk of leukemia and other benzene related‐malignancies (Shen et al ., 2008; Saadaoui et al ., 2013). The monitored level of PM10 in the present study exceeds the permissible limit of CPCB, India as well study showed significant elevated urinary benzene metabolite (phenol), oxidative stress and increased level of MtDNAcn among fuel filling attendants.…”
Section: Discussionmentioning
confidence: 99%